2018
DOI: 10.3168/jds.2017-14280
|View full text |Cite
|
Sign up to set email alerts
|

Is rumination time an indicator of methane production in dairy cows?

Abstract: As long as large-scale recording of expensive-to-measure and labor-consuming traits, such as dry matter intake (DMI) and CH 4 production (CH 4 P), continues to be challenging in practical conditions, alternative traits that are already routinely recorded in dairy herds should be investigated. An ideal indicator trait must, in addition to expressing genetic variation, have a strong correlation with the trait of interest. Our aim was to estimate individual level and phenotypic correlations between rumination tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
12
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
5
12
2
Order By: Relevance
“…Animals that ruminate longer tend to exhale less CH 4 (MeC and MeP). This result differs from that of Zetouni et al (2018), who showed a null association between MeP and RT. Some of the factors that influence CH 4 production can also affect rumination time.…”
Section: Genetic Correlations Between Ch 4 and Other Traitscontrasting
confidence: 99%
“…Animals that ruminate longer tend to exhale less CH 4 (MeC and MeP). This result differs from that of Zetouni et al (2018), who showed a null association between MeP and RT. Some of the factors that influence CH 4 production can also affect rumination time.…”
Section: Genetic Correlations Between Ch 4 and Other Traitscontrasting
confidence: 99%
“…According to other authors [13,26,45], hot climate conditions cause a depressive effect on dry matter intake because the reduction of time spent at feeding reduces the dry matter intake. Moreover, Zetouni et al [46] proved how there is a high correlation between CH 4 production and dry matter intake; consequently, the observed decrease in CH 4 production between W1 and W2 in this study could be ascribed to a reduction of dry matter intake due to hot climate conditions.…”
Section: Effect Of Cbbm On Gas Concentrationssupporting
confidence: 57%
“…The tags record the amount of time a cow spends chewing the cud and are thus implicated in CH 4 emissions through the digestion and fermentation of fibre. Interestingly, Zetouni et al (2018a) compared the rumination time (415.1 ± 116.7; mean ± SD) with CH 4 production (405.2 ± 115.8), with these similar means and variances being promising. However, estimates of individual level correlations were very close to zero (−0.10 ± 0.07).…”
Section: Improving the Selection Accuracy Of Ch 4 Emissionsmentioning
confidence: 87%